Motivational aspects of wintering in polar stations - Walotek, Alicja; Skorupa, Agnieszka; Barros-Delben, Paola (Polish Polar Research, 2024)
For over one hundred years, humans have been actively exploring polar regions. At present, each year, several thousand people work at polar stations in the Arctic and Antarctica. Polar stations have unique workplace characteristics; the conditions are classified as isolated, confined, and extreme. This leaves the important question of what motivates people to carry out professional tasks in such a context, particularly during wintering over in a polar station. The current study was designed to answer that question. Eighty-six winterers (22 women and 64 men) from ten different countries described their motivation to winter over. The qualitative approach, thematic analysis, was applied to data analysis. Two coding cycles were applied: initial coding and theming of the data. Fifty-six detailed categories were identified and then grouped thematically, resulting in 17 main categories. The three main motivation categories were challenge and adventure (N = 36), unique experience (N = 16), and performance of the job (N = 15). There were also differences in motivation between explorers from different countries, from Arctic and Antarctic polar stations, from civilian and military polar stations, and between female and male polar expeditioners. Obtained results can be applied to improve selection procedures and better support expeditioners during their stay in the polar station.